2016
DOI: 10.1016/j.cell.2016.07.046
|View full text |Cite|
|
Sign up to set email alerts
|

γδ T Cells Support Pancreatic Oncogenesis by Restraining αβ T Cell Activation

Abstract: Summary Inflammation is paramount in pancreatic oncogenesis. We identified a uniquely-activated γδT cell population which constituted ∼40% of tumor-infiltrating T cells in human pancreatic ductal adenocarcinoma (PDA). Recruitment and activation of γδT cells was contingent on diverse chemokine signals. Deletion, depletion, or blockade of γδT cell recruitment was protective against PDA and resulted in increased infiltration, activation, and Th1-polarization of αβT cells. Whereas αβT cells were dispensable to out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
278
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(293 citation statements)
references
References 43 publications
12
278
3
Order By: Relevance
“…As elegantly indicated in a recent review (58), murine models using human cells have shortcomings, such as harboring impaired immune infiltrates (e.g., lymphocytes, natural killer cells). This is particularly important, as a complex relationship exists between the immune system and pancreatic cancer development, and these complex interactions have important implications for disease progression and control (59,60). For example, CD8 + T cells and Th1-polarized CD4 + T cells mediate tumor protection in murine pancreatic cancer models and are associated with prolonged survival in humans (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…As elegantly indicated in a recent review (58), murine models using human cells have shortcomings, such as harboring impaired immune infiltrates (e.g., lymphocytes, natural killer cells). This is particularly important, as a complex relationship exists between the immune system and pancreatic cancer development, and these complex interactions have important implications for disease progression and control (59,60). For example, CD8 + T cells and Th1-polarized CD4 + T cells mediate tumor protection in murine pancreatic cancer models and are associated with prolonged survival in humans (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Peri-pancreatic lymphocyte subsets have divergent effects on tumorigenesis by either suppressing cancer growth via antigen-restricted tumoricidal immune responses (CD8 + T-cells and Th1-polarized CD4 + T-cells) or by promoting tumor progression via induction of immune suppression (myeloid-derived suppressor cells; MDSCs and Th2-deviated CD4 + T-cells) (76,77). Another study showed that pancreatic adenocarcinoma-infiltrating γδ-T cells are a highly influential lymphocyte subset promoting pancreatic oncogenesis and reducing survival via novel cross-talk with the adaptive immune compartment; Nevertheless, they may also have prognostic significance of survival and response to immunotherapeutic regimen (77). Investigators from our Institution have reported an association between tumorassociated neutrophils (TANs) and advanced IPMN lesions (78).…”
Section: Peripheral Blood Cellmentioning
confidence: 99%
“…13 Along similar lines, gd T cells abundantly infiltrated mouse PDAs generated by the orthotopic implantation of malignant cells from Pdx1 Cre ;Kras G12D ;Tp53 R172H (KPC) mice (which spontaneously develop invasive PDAs by 8 weeks of age) into syngeneic immunocompetent hosts. In this system, gd T cells exhibited a peculiar phenotype (as compared to splenic gd T cells), as they were characterized by the upregulation of FAS ligand (FASLG), killer cell lectin-like receptor subfamily B member 1C (KLRB1C, best known as NK1.1), ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, best known as CD39), junction adhesion molecule like (JAML), and TNF receptor superfamily member 4 (TNFRSF4, best known as OX40), as well as by enriched FOXP3…”
Section: Cd8mentioning
confidence: 95%
“…Similar observations were obtained in 6-month-old Ptf1a Cre ;Kras G12D (KC) mice, a model of preinvasive PDA. 13 Of note, KPC-derived cells orthotopically implanted into Ccr2 ¡/¡ , Ccr5 ¡/¡ , or Ccr6 ¡/¡ mice recruited limited amounts of gd T cells as compared to KPC-derived PDAs established in wild-type (WT) mice, demonstrating the importance of chemokine signaling in this setting. 13 To test whether gd T cells would play an etiologic role in pancreatic carcinogenesis, Daley and collaborators crossed KC mice with Tcrd ¡/¡ mice (which lack gd T cells but contain normal amounts of ab T lymphocytes).…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation